2013
DOI: 10.3386/w19373
|View full text |Cite
|
Sign up to set email alerts
|

Health Insurance for "Humans": Information Frictions, Plan Choice, and Consumer Welfare

Abstract: Traditional models of insurance choice are predicated on fully informed and rational consumers protecting themselves from exposure to financial risk. In practice, choosing an insurance plan from a set of complex non-linear contracts is a complicated decision often made without full information on several potentially important dimensions. In this paper we combine new administrative data on health plan choices and claims with unique survey data on consumer information and other typically unobserved preference fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
188
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(203 citation statements)
references
References 26 publications
15
188
0
Order By: Relevance
“…Given the older age of respondents, however, it is unclear whether these and other findings pertaining to Medicare will generalize to younger, likely less cognitively impaired, populations. Another study (Handel and Kolstad, 2013), found that only a minority of workers at a large firm were able to accurately answer questions on benefit design, their own recent health care cost, or other key questions that should, in principal, have been relevant to their choice of health insurance. This lack of understanding was correlated with their insurance choices.…”
Section: Prior Researchmentioning
confidence: 99%
“…Given the older age of respondents, however, it is unclear whether these and other findings pertaining to Medicare will generalize to younger, likely less cognitively impaired, populations. Another study (Handel and Kolstad, 2013), found that only a minority of workers at a large firm were able to accurately answer questions on benefit design, their own recent health care cost, or other key questions that should, in principal, have been relevant to their choice of health insurance. This lack of understanding was correlated with their insurance choices.…”
Section: Prior Researchmentioning
confidence: 99%
“…Pauly and Blavin (2008) and Baicker, Mullainathan, and Schwartzstein (2015) summarize evidence that people have a systematic propensity to under-or overuse certain treatments at the margin. For example, Choudhry et al (2011) document that many recent heart attack victims do not adhere to drug Handel and Kolstad (2015b) "Uninformed" consumers leave substantial dollars on table when "over-choosing" generous insurance coverage, relative to "informed" consumers.…”
Section: Consumer Ignorance and Misinformation In Health Marketsmentioning
confidence: 99%
“…Going forward, we envision more work emerging in this area, as more field data become available, and researchers are granted ways to design surveys that can reach (a subset of) subjects in the field data (e.g., as in Handel and Kolstad 2015).…”
Section: Combining Experimental and Field Datamentioning
confidence: 99%
“…For example, Handel and Kolstad (2015) study the effect of information frictions and hassle costs, measured via a survey administered to individuals for whom health-insurance information is available. The survey elicits individuals' information about available medical providers/treatments and perceived time and hassle costs to learn the characteristics of a high-deductible health-insurance plan (which is cheaper than the other options).…”
mentioning
confidence: 99%